(untitled) (LSP International Journal, 2017)
Industrial training, or internship program, is always a must in any academic institutions, especially those offering engineering programs. Since industrial training is always structured at the end of the program, students going for internships are considered to be already well prepared with the content knowledge of their field of study. However, the job scope of an engineer does not entail content knowledge only. An engineer still has to carry out various other tasks like writing reports and letters as well as participating in meetings or discussions; thus the needs to ensure that these trainees are competent in the English language and effective as communicators. However, which English communication skills in particular do the industries in general require of these students? Venkatraman&Prema (2007) claim that “In the globalized context, students of Engineering and Technology need a specific set of language skills for their success in education and career.” All academic institutions should balance their curricula between future professionals and workplace needs of their graduates (Kaneko, Rozycki& Orr, 2008). In light of this, this paper will look at the English language needs of 18 organisations related to the chemical engineering industry where industrial trainees from Universiti Kuala Lumpur Malaysian Institute of Chemical & Bioengineering Technology (UniKL MICET) were sent to. A survey conducted found that all but one of the organisations see that English language is important even though not all of them use the language at work. This paper discusses the tasks in which English language is most required and what language functions are most commonly used in the organisations. Trainees’ feedback on the actual usage of English language while they are on industrial training for three months will also be discussed.